Some Linear Programming Techniques in Fuzzy Environment - Bhatia, Neha (My University, 2012)
In this thesis, shortcomings and limitations of the existing methods for solving as well as the existing methods to deal with the sensitivity analysis of such linear programming problems in which parameters or decision variables or both are represented by fuzzy numbers are pointed out. Also, some new methods are proposed to resolve these shortcomings as well as to overcome these limitations.
phd, smca
Keywords: Fuzzy Linear Programming Problems; Fuzzy Sensitivity Analysis; Fuzzy Transportation Problems